Squamata (Reptilia) from four sites in southern Amazonia, with a biogeographic analysis of Amazonian lizards - Ávila-Pires, Teresa Cristina Sauer de (Museu Paraense Emílio Goeldi, 2010)
We studied the squamate fauna from four sites in southern Amazonia of Brazil. We also summarized data on lizard faunas for nine other well-studied areas in Amazonia to make pairwise comparisons among sites. The Biogeographic Similarity Coefficient for each pair of sites was calculated and plotted against the geographic distance between the sites. A Parsimony Analysis of Endemicity was performed comparing all sites. A total of 114 species has been recorded in the four studied sites, of which 45 are lizards, three amphisbaenians, and 66 snakes. The two sites between the Xingu and Madeira rivers were the poorest in number of species, those in western Amazonia, between the Madeira and Juruá Rivers, were the richest. Biogeographic analyses corroborated the existence of a well-defined separation between a western and an eastern lizard fauna. The western fauna contains two groups, which occupy respectively the areas of endemism known as Napo (west) and Inambari (southwest). Relationships among these western localities varied, except between the two northernmost localities, Iquitos and Santa Cecilia, which grouped together in all five area cladograms obtained. No variation existed in the area cladogram between eastern Amazonia sites. The easternmost localities grouped with Guianan localities, and they all grouped with localities more to the west, south of the Amazon River.